2001
DOI: 10.1021/bi0115232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phosphorylation and Mutation R145G on Human Cardiac Troponin I Function

Abstract: We have studied functional consequences of the mutations R145G, S22A, and S23A of human cardiac troponin I (cTnI) and of phosphorylation of two adjacent N-terminal serine residues in the wild-type cTnI and the mutated proteins. The mutation R145G has been linked to the development of familial hypertrophic cardiomyopathy. Cardiac troponin was reconstituted from recombinant human subunits including either wild-type or mutant cTnI and was used for reconstitution of thin filaments with skeletal muscle actin and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 34 publications
5
74
1
2
Order By: Relevance
“…In addition, we have demonstrated that the Ca 2ϩ sensitivity of E99K actin-containing thin filaments was uncoupled from the PKA-dependent phosphorylation of troponin I. Uncoupling has been reported with other HCM-or DCM-causing mutations in thin filament proteins (16,28,46), and in DCM it seems to be the only consistent effect of disease-causing mutations (21). In contrast, HCM mutations are always associated with higher myofibrillar Ca 2ϩ sensitivity.…”
Section: Actc E99k Mouse Model Of Hcm-we Developed Thementioning
confidence: 60%
See 1 more Smart Citation
“…In addition, we have demonstrated that the Ca 2ϩ sensitivity of E99K actin-containing thin filaments was uncoupled from the PKA-dependent phosphorylation of troponin I. Uncoupling has been reported with other HCM-or DCM-causing mutations in thin filament proteins (16,28,46), and in DCM it seems to be the only consistent effect of disease-causing mutations (21). In contrast, HCM mutations are always associated with higher myofibrillar Ca 2ϩ sensitivity.…”
Section: Actc E99k Mouse Model Of Hcm-we Developed Thementioning
confidence: 60%
“…Uncoupling was previously reported in the TNNTI3 R145G mutation (46) and the TNNC1 L29Q mutation (40) that cause HCM but also in DCM mutations (ACTC E361G, TNNC1 G149D, and TPM1 E40K (16,21,28)) and in troponin from human myectomy samples (56). Thus, it appears that uncoupling may be a default consequence of structural perturbations.…”
Section: Actc E99k Mouse Model Of Hcm-we Developed Thementioning
confidence: 70%
“…A recent report by Deng et al (46) showed that the TnI R145G mutation renders the actomyosin system at maximum Ca 2ϩ activation insensitive to protein kinase A phosphorylation suggesting that muscles containing this TnI mutation might have an altered response to this intracellular phosphorylation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that the R145G mutation prevents the inhibitory region of cTnI from properly interacting with actin-tropomyosin in the thin filament. In addition, cTnI carrying the R145G mutation is insensitive to phosphorylation of the two adjacent Ser residues in the cardiac N-extension [52]. Thus, replacement of a basic Arg residue in the inhibitory region of cTnI with Gly appears to disrupt the effect of PKA phosphorylation at Ser-23/Ser-24 in the cardiac N-extension.…”
Section: Molecular Mechanisms Of the Effects Of Ctni Phosphorylation mentioning
confidence: 99%